Teachers’ Strategies in Developing and Measuring Students’ Communication Skills - Hery Rosdianti; Wuri Wuryandani; Heri Retnawati (Al Ibtida: Jurnal Pendidikan Guru MI, 2020)
AbstractA good communication skill is one of the capabilities that must be mastered by students to be able to socialize, adapt, and compete with others in the scope of school and social life in the 21st century. The purpose of this type of descriptive qualitative research was about to describe the teachers' strategies in developing and conducting an assessment related to the communication skills of elementary school students in Indonesia. Data were obtained through interviews with 10 elementary school teachers in Yogyakarta Province. Data analysis was performed through applying data analysis steps proposed by Bogdan and Biglen. The results showed that an effective strategy that teachers could use to develop students' communication skills was through discussion and presentation methods. Meanwhile, the assessment of students' communication skills is integrated to cognitive, affective, and psychomotor assessments both in terms of instruments and time of assessment. This was resulted from various limitations originating of the teacher and the availability and completeness of school facilities and infrastructure that supports the implementation of various kinds of assessment.Keywords: assessment, communication skills, elementary school students. AbstrakKeterampilan komunikasi yang baik adalah salah satu kemampuan yang harus dikuasai oleh siswa untuk dapat bersosialisasi, beradaptasi dan bersaing dengan orang lain dalam ruang lingkup sekolah maupun kehidupan sosial di abad ke-21. Tujuan dari penelitian deskriptif kualitatif ini adalah untuk mendeskripsikan strategi guru dalam mengembangkan dan melakukan penilaian terkait kemampuan komunikasi peserta didik Sekolah Dasar di Indonesia. Data diperoleh melalui wawancara yang bersumber dari 10 orang guru sekolah dasar di Provinsi Yogyakarta. Analisis data dilakukan dengan menerapkan langkah-langkah analisis data yang dikemukakan oleh Bogdan dan Biglen. Hasil penelitian menunjukkan bahwa strategi efektif yang dapat digunakan guru untuk mengembangkan kemampuan komunikasi siswa adalah melalui pembelajaran diskusi dan presentasi. Sedangkan penilaian kemampuan komunikasi siswa dilakukan secara terintegrasi dengan penilaian kognitif, afektif dan psikomotor baik dalam hal instrumen maupun waktu penilaian. Hal tersebut disebabkan oleh berbagai keterbatasan yang berasal dari guru dan ketersediaan serta kelengkapan sarana dan prasarana sekolah yang mendukung keterlaksanaan berbagai macam penilaian.Kata kunci: penilaian, kemampuan komunikasi, siswa sekolah dasar.